Inhibition of differentiation of monocyte-derived macrophages toward an M2-Like phenotype May Be a neglected mechanism of β-AR receptor blocker therapy for atherosclerosis - Liu, Shouyi; Zhang, Bo; Zhou, Jingqun; Lv, Jianfeng; Zhang, Jinxia; Li, Xiangyan; Yang, Weihua; Guo, Yuanlin (Frontiers in Pharmacology, 2024)
The clinical efficacy of adrenergic β-receptor (β-AR) blockers in significantly stabilizing atherosclerotic plaques has been extensively supported by evidence-based medical research; however, the underlying mechanism remains unclear. Recent findings have highlighted the impact of lipid-induced aberrant polarization of macrophages during normal inflammatory-repair and regenerative processes on atherosclerosis formation and progression. In this review, we explore the relationship between macrophage polarization and atherosclerosis, as well as the influence of β-AR blockers on macrophage polarization. Based on the robust evidence supporting the use of β-AR blockers for treating atherosclerosis, we propose that their main mechanism involves inhibiting monocyte-derived macrophage differentiation towards an M2-like phenotype.